Recursos enunciativo-discursivos em manchetes que divulgam resultados de pesquisas de intenção de voto - Silveira, Marcelo Moreira da (2020)
The objective of this research was to know the enunciative-discursive resources used in the construction of headlines that aim at the dissemination of the results of polls of intention to vote. In addition, the objective was to explain the strength of adhesion present in these resources, as well as to identify which ones are recurrent in the constitution of these statements. The analysis corpus consists of three headlines that cover the same theme - the results of the poll of intention to vote, carried out by Datafolha between April 11 and 13, 2018. The analysis material was taken from three different journals: Folha de S. Paulo, O Globlo and Diário do Centro do mundo. The theoretical framework on which the research is based is Discourse Analysis of the French line, more specifically in the perspective adopted by Dominique Maingueneau and Patrick Charaudeau. The results revealed that the reported saying, the direct speech, the highlighted statement, the scenography, the staging of the information and the discursive ethos - as categories of analysis of the DA - are recurrent enunciative-discursive resources in the analysis material. The studies also revealed the commitment of the media to give visibility to the event with the greatest impact at the time - the presidential elections - with credibility. However, it was found that the media construction of information in these headlines was also committed to capturing the reader's attention and interest. It was also evident that the enunciative-discursive choices made in the headlines, in addition to aiming at the readers' adherence, sought to legitimize the positions of the enunciators themselves